Devir cigano: o encontro cigano-não cigano (rom-gadjé) como elemento facilitador do processo de individuação - Silva, Valeria Sanchez (2006)
This work stands on the individuation process, facilitated for the alterity relation crossing the gipsy non-gipsy ways (rom-gadjé). This thematic was sketched from internal images and was configured with the necessity of experimentation. The empiric cerne of this work was developed through an inter-ethnic coexistence from 1992 to 2003. Jung´s analytical theoretical recital opened the possibilities of dialectics for the understanding of this alterity, which has became a mirror in the difference of shade that the other induces